(untitled) - Vũ Bội Tuyền (Hà Nội, 1998)
Sách giới thiệu 20 nhà phát minh nổi tiếng thế giới như: Jean Guttenberg, Darcaro, Benjamin Franklin, Alessandro Volta, Roibert Fulton, H. Mozili, George Stephenson, Samuel F. B. Morse, Justus Libic, H. Bessemer, William Thomson, Alfred Nobel, Thomas Edison, Alexander Graham Bell, Alexander Popov, Wilbur Wright, Gugliemo Marconi, và John Baird
Keywords: inventors - biography,scientists - biography